EFFECT OF RESERVOIR UTILIZATION AND OTHER ANTHROPOGENIC ACTIVITIES ON THE HADEJIA RIVER VALLEY FLOODS: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2023)
The unceasing risk perception and socio-economic damages caused by flood disasters have been persistent in Hadejia River Valley (HRV). There is, however, a need to review upstream factors that could exacerbate downstream floods in the valley. The review tends to gain insight from the local and global flood occurrences due to the interplay between upstream reservoir management and other anthropogenic activities and downstream floods. The review underscores the impact of poor upstream reservoir operation, agriculture and other anthropogenic activities in exacerbating the occurrence of floods. These activities alter natural drainage patterns, reduce water absorption, and frequent spills from the major dams and hence, amplify runoff resulting in heightened flood risks. It was observed that reservoirs can serve as flood control facilities (if well-managed) and also exacerbate flooding by releasing large volumes of water too quickly or reaching capacity during intense rainfall events. It is, therefore, essential to consider the location, design, and operation of reservoirs, as well as their role within the HRV management context. In conclusion, the Hadejia-Jama’are River Basin Development Authority (HJRBDA) should adopt the Integrated Water Resource Management (IWRM) approach that combines reservoir management, land use, flood forecasting, and emergency response strategies for minimizing downstream flood risks and maximizing the utilization of the upstream reservoirs.
Keywords: Anthropogenic activities; Floods; Hadejia River Valley; Nigeria; Reservoir utilization